Nitrate ammonification in mangrove soils: a hidden source of nitrite? - Balk, Melike; Laverman, Anniet M.; Keuskamp, Joost A.; Laanbroek, Hendrikus J. (Frontiers in Microbiology, 2015)
Nitrate reduction is considered to be a minor microbial pathway in the oxidation of mangrove-derived organic matter due to a limited supply of nitrate in mangrove soils. At a limited availability of this electron acceptor compared to the supply of degradable carbon, nitrate ammonification is thought to be the preferential pathway of nitrate reduction. Mangrove forest mutually differ in their productivity, which may lead to different available carbon to nitrate ratios in their soil. Hence, nitrate ammonification is expected to be of more importance in high- compared to low-productive forests. The hypothesis was tested in flow-through reactors that contain undisturbed mangrove soils from high-productive Avicennia germinans and Rhizophora mangle forests in Florida and low-productive Avicennia marina forests in Saudi Arabia. Nitrate was undetectable in the soils from both regions. It was assumed that a legacy of nitrate ammonification would be reflected by a higher ammonium production from these soils upon the addition of nitrate. Unexpectedly, the soils from the low-productive forests in Saudi Arabia produced considerably more ammonium than the soils from the high-productive forests in Florida. Hence, other environmental factors than productivity must govern the selection of nitrate ammonification or denitrification. A rather intriguing observation was the 1:1 production of nitrite and ammonium during the consumption of nitrate, more or less independent from sampling region, location, sampling depth, mangrove species and from the absence or presence of additional degradable carbon. This 1:1 ratio points to a coupled production of ammonium and nitrite by one group of nitrate-reducing microorganisms. Such a production of nitrite will be hidden under the nitrate-limited conditions of most mangrove forest soils.